Children and youth with impairments in social skills and cognition in out-of-school time inclusive physical activity programs: a scoping review. (4th March 2021) - Orr, Krystn; Wright, F. Virginia; Grassmann, Viviane; McPherson, Amy C.; Faulkner, Guy E.; Arbour-Nicitopoulos, Kelly P.
Abstract : Children and youth with impairments in social skills and/or cognition face many barriers to community participation specifically physical activity (PA) (e.g., limited staff training). Inclusive PA settings may provide opportunities for children and youth with and without impairments to engage together and promote physical and social skill development. The purpose of this scoping review was to critically evaluate the literature on out-of-school PA programs (i.e., non-curriculum programming) that included children and/or youth with impairments in social skills and/or cognition. A keyword search of seven databases followed by eligibility screening led to ten articles for this scoping review. For each included study, two research team members independently extracted and synthesized the data, and appraised the study reporting quality using the published quality assessment tool (QATSDD). Experts' evaluation of the research literature was obtained. Ten studies, which varied from low to high reporting quality, collectively addressed the following outcomes, with all showing mixed impacts: anthropometrics and fitness; motor and sport skills; psychological well-being; and socialization. Experts suggested routes forward for research and practice including longitudinal designs and programming variety to meet individual needs. Out-of-school PA programs that include children and/or youth with impairments in social skills and/or cognition provide an opportunity to improve multiple areas of health and wellness. However, limited high-quality research has been conducted to-date. Further evaluation of program effectiveness is warranted.